Listening to the Ugly Voices - Park, Hee-Kyu Heidi (2016)
This is a reflective essay that responds to The Journal for Pastoral Theology editor's invitation to the Journal for Pastoral Theology boards to address the commitment of the field in the current political social climate after the presidential election of 2016.
Keywords: Wounded Healer; emotional epistemology; movement of heart; Vulnerability